Orange Juice and Hesperidin Promote Differential Innate Immune Response in Macrophages ex vivo - Zanotti Simoes Dourado, Grace Kelly [UNESP]; Abreu Ribeiro, Livia Carolina de [UNESP]; Carlos, Iracilda Zeppone [UNESP]; César, Thaís Borges [UNESP] (Verlag Hans Huber, 2013)
The purpose of this study was to verify the immune response induced by intake of orange juice or hesperidin on macrophages through the secretion of cytokines and nitric oxide. Mice were divided in three groups treated orally with orange juice, hesperidin, or control for 2 weeks. Ex vivo macrophages from all groups of mice were cultured with or without lipopolysaccharide (LPS)-stimuli, and the levels of nitric oxide (NO) and of the cytokines IL-10, IL-12, and TNF-alpha were evaluated. Macrophages of non-LPS-stimulated, orange juice treatment increased IL-12 levels by 143 % and the other cytokines and NO levels were unchanged. Hesperidin treatment increased IL-12 levels by 72 % and strongly decreased the NO secretion. For LPS-stimulated macrophages the orange juice (OJ) treatment decreased TNF-alpha secretion by 100 % and did not alter other cytokines, while NO levels increased 41 %. Hesperidin treatment decreased NO, IL-10, IL-12, and TNF-alpha levels by 56 %, 47 %, 29 %, and 63 %, respectively. In conclusion, OJ and hesperidin showed different immune responses, suggesting that hesperidin displays a suppressive effect on inflammation generated by LPS, while OJ seems to enhance the functions of macrophages associated with antimicrobial activity.
Keywords: orange juice; hesperidin; nitric oxide; cytokines; mouse